(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Covid-19 o’tkazgan dissirkulyator ensefalopatiya bilan og’rigan bemor kognitiv buzilishlarning o’ziga xosligi.